2005
DOI: 10.1098/rspb.2004.3043
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen adaptation to seasonal forcing and climate change

Abstract: Many diverse infectious diseases exhibit seasonal dynamics. Seasonality in disease incidence has been attributed to seasonal changes in pathogen transmission rates, resulting from fluctuations in extrinsic climate factors. Multi-strain infectious diseases with strain-specific seasonal signatures, such as cholera, indicate that a range of seasonal patterns in transmission rates is possible in identical environments. We therefore consider pathogens capable of evolving their 'seasonal phenotype', a trait that det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
98
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 35 publications
(37 reference statements)
0
98
0
3
Order By: Relevance
“…However, within the 01 serogroup classification, cholera cases are identified as being of a particular biotype (classical or El Tor) and of a particular serotype (Inaba or Ogawa, and very rarely Hikojima). Cholera biotypes are distinct phenotypes that differ with respect to the severity of their infections (and consequently their infectionto-case ratios), ability to survive outside the human host and seasonality patterns (Woodward & Mosley 1972;Glass et al 1982;Reidl & Klose 2002;Koelle et al 2005a). Serotypes differ from one another only with respect to antigenic determinants that are present on their O-antigen capsule.…”
Section: Introductionmentioning
confidence: 99%
“…However, within the 01 serogroup classification, cholera cases are identified as being of a particular biotype (classical or El Tor) and of a particular serotype (Inaba or Ogawa, and very rarely Hikojima). Cholera biotypes are distinct phenotypes that differ with respect to the severity of their infections (and consequently their infectionto-case ratios), ability to survive outside the human host and seasonality patterns (Woodward & Mosley 1972;Glass et al 1982;Reidl & Klose 2002;Koelle et al 2005a). Serotypes differ from one another only with respect to antigenic determinants that are present on their O-antigen capsule.…”
Section: Introductionmentioning
confidence: 99%
“…15 16 These findings have consequences for the impact climate change might have on the dynamics 17 of epidemics. Koelle et al (2005) state that increased mean global air temperature due to 18 climate change, likely leads to higher disease transmission and relaxation of the pathogen's 19 overwintering restrictions. The combination of the two then increases disease severity.…”
mentioning
confidence: 99%
“…Seasonal disease variations may come about as the result of many factors, including seasonally heightened host susceptibility resulting from seasonal stressors [70], changes in contact rates resulting from school terms in the case of childhood diseases [71] and seasonal changes in pathogen transmission rates resulting from climate variation [72]. Temperature, which is the main climate change driver, can affect disease by altering the susceptibility of hosts, the virulence of pathogens and the growth rates of both hosts and pathogens, which can in turn influence host pathology and disease emergence [73,74].…”
Section: Climate Change Effects On Pathogen Strains Host-pathogen Inmentioning
confidence: 99%
“…In Bangladesh, strains within the 01 serogroup of cholera are designated as being either of the "Classical" or the "El Tor" biotype, and both biotypes are affected by differing seasonal signatures with pronounced seasonality in disease incidence [72,77]. The Classical strain was believed to be the dominant strain until the 1970s, when it was replaced by the El Tor strain which is more resilient to fluctuations in water quantity and quality, as evidenced by the less pronounced seasonal variability of its reproductive rates [70]. As such, Koelle and colleagues [70] have shown that the cholera strain sensitivity to environmental fluctuations can be considered a phenotypic character trait subject to evolution.…”
Section: Climate Change Effects On Pathogen Strains Host-pathogen Inmentioning
confidence: 99%